The spiritual Emerson : essential writings - Emerson, Ralph Waldo, 1803-1882 (Beacon Press, 2003)
Collects selected essays by Ralph Waldo Emerson that pertain to his views of spirituality, including "Self-Reliance," "Compensation," and "Worship."